THE PARENTAL INVOLVEMENT IN FACILITATING LANGUAGE EXPOSURE FOR A LEARNER’S SPEAKING ABILITY (A CASE STUDY ON A 9-YEAR-OLD CHILD) - Alrosanty, Karunia Sholihah; Susilawati, Endang; Wardah, Wardah (Journal of English Education Program, 2021)
This research aimed to discover the parental involvement from the mother in facilitating the language exposure to improve the learner’s speaking ability. This research was a case study and applied the procedure from Yin to design steps of this research: planning, designing, collecting, analyzing, and sharing. The researcher interviewed the learner’s mother using the interview guidelines and observed the daily activity. Therefore, the researcher discovered that using English in daily conversation, supporting the learner when using English during the daily conversation and teaching-learning process, using English during the teaching-learning process, providing media to support the learner, stimulating English to the learner, and assisting or monitoring the learner when using the media provided a good amount of language exposure for the learner to improve his speaking skill, especially his fluency and its function in transaction and interaction. These parental involvements worked in one unity like a chain reaction to build a language exposure that would expose the learner and improve the learner’s speaking.